Supporting children and youth during the COVID-19 pandemic and beyond: A rights-centred approach. Issue 6 (5th August 2020) - Suleman, Shazeen; Ratnani, Yasmine; Stockley, Katrina; Jetty, Radha; Smart, Katharine; Bennett, Susan; Gander, Sarah; Loock, Christine
Abstract: The COVID-19 pandemic is an unprecedented global crisis, affecting millions globally and in Canada. While efforts to limit the spread of the infection and 'flatten the curve' may buffer children and youth from acute illness, these public health measures may worsen existing inequities for those living on the margins of society. In this commentary, we highlight current and potential long-term impacts of COVID-19 on children and youth centring on the UN Convention of the Rights of the Child (UNCRC), with special attention to the accumulated toxic stress for those in difficult social circumstances. By taking responsive action, providers can promote optimal child and youth health and well-being, now and in the future, through adopting social history screening, flexible care models, a child/youth-centred approach to "essential" services, and continual advocacy for the rights of children and youth.